2017
DOI: 10.1001/jamainternmed.2017.5512
|View full text |Cite
|
Sign up to set email alerts
|

Association of Warfarin Use With Lower Overall Cancer Incidence Among Patients Older Than 50 Years

Abstract: In cancer models, warfarin inhibits AXL receptor tyrosine kinase-dependent tumorigenesis and enhances antitumor immune responses at doses not reaching anticoagulation levels. This study investigates the association between warfarin use and cancer incidence in a large, unselected population-based cohort.OBJECTIVE To examine the association between warfarin use and cancer incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 36 publications
2
71
0
9
Order By: Relevance
“…We screened 2,389 titles and abstracts and selected 29 studies for full–text screening (Appendix B, Supporting Information). Of these, 6 studies were included . We excluded 18 studies that did not report original data, e.g.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We screened 2,389 titles and abstracts and selected 29 studies for full–text screening (Appendix B, Supporting Information). Of these, 6 studies were included . We excluded 18 studies that did not report original data, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…prostate cancer survival, and 1 study that reported a composite outcome of urogenital malignancies but not prostate cancer specifically . We identified 2 eligible studies from cross–referencing resulting in a total of 8 included studies; 7 observational studies and 1 secondary analysis of data from a randomized controlled trial . In the secondary analysis of the randomized trial, patients were assigned to either 6 weeks (n = 419) or 6 months (n = 435) of VKA therapy after first occurrence of venous thromboembolic disease and followed for occurrence of cancer for a mean of 8.1 years from recruitment .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations